Clinicopathological characteristics of ypT0N0 urothelial carcinoma following neoadjuvant chemotherapy and cystectomy. Issue 8 (4th June 2019) - Magers, Martin J; Kaimakliotis, Hristos Z; Barboza, Marcelo P; Bandali, Elhaam; Adra, Nabil; Koch, Michael O; Cheng, Liang
Abstract : Aims: To describe a large tertiary care academic centre's experience with patients who achieve a complete pathological response (ie, ypT0N0) following neoadjuvant chemotherapy (NAC) and radical cystectomy (RC) with emphasis on morphological features present in the RC and clinical outcome. Methods: 41 patients with ypT0N0 disease following transurethral resection of bladder tumour (TURBT), NAC and RC with available clinical follow-up information were analysed. Slides from all RCs were reviewed to confirm pathological stage and assess for morphological parameters (eg, foreign body giant cell reaction, dystrophic calcification, scar and fat necrosis). Results: With median follow-up of 32.8 months, the recurrence-free survival at 1 and 5 years was 97.4% and 93.5%, while the overall survival at 3 and 5 years was 94.2% and 88.6%, respectively. No patients died of urothelial carcinoma. Stage assigned at TURBT was 1 pTa (2%), 1 pT1 (2%), 38 pT2 (93%) and 1 pT3a (2%). 17 TURBTs demonstrated variant histology, with the majority of these being squamous (65%). The most common morphological features present at RC were scar (100%), foreign body giant cell reaction (80%), chronic inflammation within lamina propria (68%) and dystrophic calcifications (39%). Other morphological features were less common or absent. Conclusion: ypT0N0 disease at RC portends an excellent prognosis, regardless of stage or variant histology in the TURBT; scar, foreign body giant cell reaction, chronic inflammation and dystrophic calcifications are often present.